PERAN KEGIATAN OPERASIONAL KREDIT DALAM MENDUKUNG KELANCARAN ADMINISTRASI KREDIT: PENGALAMAN MAGANG DI PT BANK RAKYAT INDONESIA (PERSERO) TBK BRANCH OFFICE PALANGKA RAYA - Fifi Tri Wulandari; Evinalia Yeba (Jurnal Pengabdian Masyarakat Berkelanjutan, 2026)
The Independent Impact Internship program is designed as a vehicle for experiential learning to align students' academic competencies with the real needs of the banking industry. This field practice-based study aims to analyze the configuration of credit operational workflows, the integration mechanism of digital archiving systems, and the resolution of administrative constraints at PT Bank Rakyat Indonesia (Persero) Tbk Palangka Raya Branch Office. The method used in this study is descriptive qualitative with a participatory case study design, where primary data was collected directly through participatory observation and daily logbook records over a four-month period, from January 22 to May 26, 2026. The implementation results indicate that the credit operational architecture at the branch office operates under the Prudential Banking Principle using an assembly line system. The smoothness of liquidity disbursement at the front line highly depends on the administrative order of the back office, which includes legal document validation, registration of bookkeeping documents (UM06), digital archive migration into the Brimen application ecosystem, and physical management of collateral documents in fireproof rooms. Nevertheless, operational service efficiency still faces several technical bottlenecks, such as centralized wet-signature-based authorization, the risk of physical document accumulation due to high daily input volumes, and the lengthy turnaround time for processing pre-auction files at external agencies. As a solution, technological optimization through digital signature acceleration, restructuring daily scanning workloads, and establishing formal Service Level Agreements (SLA) with local bureaucratic agencies are crucial for sustainable implementation.